Age and connection to nature: when is engagement critical?. Issue 5 (1st April 2019) - Hughes, Joelene; Rogerson, Mike; Barton, Jo; Bragg, Rachel
Abstract : Conservation organizations are increasingly aware of the need to motivate pro‐environmental behavior by connecting people with nature. However, to maximize the effectiveness of the limited resources available, there needs to be a better understanding of the variability in people's connection to nature shown at different ages. We examined connection to nature among people aged 5–75 years, using two popular measures, in a cross‐sectional UK sample, based on the hypothesis that there would be clear, age‐related patterns in people's connection to nature, with specific "breakpoints" associated with differences in feelings of connection. Data were collected across a variety of locations. Analysis of generalized additive models revealed similar age‐related patterns for both measures, with connection declining from childhood to an overall low in the mid‐teens, followed by a rise to the early 20s and reaching a plateau that lasts to the end of the lifetime. Both measures also showed that females generally had higher connection scores than males. These findings have implications for conservation action.